Sensor-assessed grasping time as a biomarker of functional impairment in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Tascilar, Koray; Phutane, Uday; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; Schett, Georg; et al. (Scientific Reports, 2025)
Quantifying physical impairment in rheumatoid arthritis (RA) is important to determine disease burden and disability. Therefore, we aimed to define hand function impairments in RA patients using an opto-electronic measurement system (OMS). In this cross-sectional pilot study, spatio-temporal and hand segment data were collected during the fine motor skill Moberg Picking-Up Test (MPUT) and two elementary hand movement tasks in RA patients and healthy controls (HC) using a marker-based OMS. The duration of two MPUT movement phases (grasping, transporting 12 objects) and kinematic characteristics during the elementary movements were evaluated. We analyzed between-group differences using linear mixed-effects models accounting for within-participant clustering of hands and adjusting for age and sex. Measurements were obtained from 24 RA and 23 HC. The mean duration of the grasping phase of MPUT was longer in RA patients compared to HC while transporting times were identical, showing a significant group-phase interaction (p < 0.001). Interphalangeal joint angle ratios were similar in RA and HC (p > 0.05) with a lower ratio in both groups for the task thumb-finger opposition compared to flexion of joints. In RA patients especially grasping objects was impaired, and performance time for a subset of objects may serve as a quantitative biomarker of functional impairment.<br
CRIS-Team Scopus Importer:2025-03-14
Keywords: Biomarkers; Biomechanics; Fine-motor skills; Hand; Rheumatoid arthritis